Floristic Diversity, Community Characteristics and above Biomass of Woody Species in Subtropical forests of Ziro Valley, Arunachal Pradesh - Yam, Gyati; Tripathi, O. P. (Indian Forester, 2015)
Present study was conducted during 2011-2012 in subtropical forests for enumeration of floristic diversity, community characteristics and above ground biomass (AGB) analysis. Random sampling approach was adopted. Altogether 97 species were recorded from the sampled area (0.3 ha) and species richness was higher at woody (60 species) layer than other layer of forest. Majority of species showed low frequency followed by later frequency classes. Dominance distribution curve for woody species was log-normal while it was broken-stick model for shrubs and ground species. Majority of species showed clumped spatial distribution pattern. Stand density of woody species was 1607 individuals ha-1 and basal cover was 68.07 m2 ha-1 . Density-diameter distribution of woody species differed markedly. Lower diameter individuals have contributed maximum of the total stand density however, 55% of the basal cover was added by intermediate diameter class. Diversity index was recorded highest for woody species and minimum for the shrubs/sapling layer while dominance and evenness index resulted reverse trend. Total AGB and carbon of woody species was 575.05Mg ha-1 and 287.53Mg C ha-1 respectively. Individuals having diameter <20cm contributed about 71% of total stand density while contribution to total AGB was only 23%. Although individuals having >50cm were low in the forest but contributed 33% of the total AGB. Distribution of AGB carbon in different population age class followed similar pattern to that of AGB distribution.